MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI SENAM RITMIK - Asmah, Eneng Sri Susilawati, Suci Aprilyati Ruiyat (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
This study aims to improve the gross motor skills through. This type of research is Classroom Action Research (PTK) according to Kemmis and Mc Taggart. The subjects in this study were children of the group B PAUD Al-Hidayah Jawilan District, Serang District, Banten Province for the 2023/2024 school year, which consisted of 12 children, 6 boys and 6 girls. This action research was conducted in two cycles. Data analysis techniques using qualitative and quantitative descriptive analysis techniques. Qualitative data analysis is used for qualitative data in the form of observations and field notes. Quantitative data analysis is used for quantitative data obtained from the results of data collection by measuring and calculating the recapitulation of the percentage of children from sra cycles 1 and ll cycles from the results of the observations of researchers.This research was conducted because the character of the children in group B PAUD Dwi Cahyani not yet able to socialize with friendsd .The results of the analysis that has been carried out for 4 meetings in cycle I and 4 meetings in cycle II show that there has been an increase in increasing fine motor skills through. This can be seen from the results of the average percentage in children's learning activities, with a pre- cycle percentage of 36 %, an increase in cycle I it became 54,2 % then it increased again in cycle II to 82,86 %.